Early childhood education and care of children with normal and abnormal development in Poland – its importance and barriers - BUCHNAT, MARZENA; WOJCIECHOWSKA, ANETA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Marzena Buchnat, Aneta Wojciechowska, Early childhood education and care of children with normal and abnormal development in Poland – its importance and barriers. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019.Pp. 67-81. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.04 The article presents a discussion on the importance of early therapeutic interactions for the development of a child at risk of disability or with a disability and his/her family. It indicates the importance of the time of taking action in relation to a child with developmental disorder for the period from birth to the age of three years. The article pays special attention to the place of early intervention and early support in the development process, its preventive, compensatory and corrective role. It describes barriers to the development of this system in Poland and points to potential solutions to these difficulties.